Temperature sensor based on lifetime measurement of erbium fluorescence - Harun, Sulaiman Wadi; Yasin, Moh; Hamzah, Azura; Arof, Hamzah; Ahmad, Harith (INOE, 2011)
A fluorescence based fiber-optic temperature sensor is demonstrated using a modulated pump laser in conjunction with a piece of Erbium-doped fiber (EDF). The remote fiber sensor is based on a lifetime measurement of 90 cm long EDF, which is diode-pumped by a 980 nm laser and can be used to measure temperature in the range of 26°C to 60°C. The sensitivity of the sensor is obtained at 0.009 ms/°C with a linearity of more than 94%. The use of fibers of this type opens up significant possibilities for high temperature sensor probes, which is effective and useful for its high resolution and precision.